(untitled) (The Agriculturists, 2012)
Two potato varieties namely Cardinal and Heera were used in the Agrobacterium-mediated genetic transformation experiment to investigate the genetic transformation ability in the Biotechnology laboratory of the Department of Biotechnology, Bangladesh Agricultural University, Mymensingh, Bangladesh during 2006 to 2007. Agrobacterium tumefaciens strain LBA 4404 having a binary vector pB1121 of 14 KDa containing selectable marker gene npt II (neomycine phosphotransferase II) conferring kanamycin resistance, and the CIPK antisense gene encoding calcineurin B-like protein were used. Leaf and internodes were used as explants. Expression of the transgene (GUS) was confirmed by histochemical analysis. The variety Cardinal was found more suitable for expressing best GUS response (80% GUS positive) over Heera. DOI: http://dx.doi.org/10.3329/agric.v10i1.11068 The Agriculturists 2012; 10(1): 81-86